Effect of sexual health education on sexual function and resumption of sexual intercourse after childbirth in primiparous women - Zahra Pahlavani Sheikhi; Ali Navidian; Mahnaz Rigi (Journal of Education and Health Promotion, 2020)
INTRODUCTION: A large number of women experience sexual health problems during the postpartum period. This study aimed to evaluate the effect of sexual health education on sexual function and time of sexual intercourse resumption after childbirth in primiparous women in Southeast Iran. MATERIALS AND METHODS: This randomized clinical trial was conducted on 94 primiparous women randomly divided into two groups of intervention and control. The intervention group was subjected to three training sessions 3–5, 10–14, and 30–45 days after childbirth ( first session lasting 20 min and other sessions 60 min). On the other hand, the participants in the control group only received the routine postpartum training. The Female Sexual Function Index (FSFI) was completed by all participants before and 8 weeks after the intervention. Data were analyzed in SPSS software (version 22) using descriptive and inferential statistics, such as Chi-square test, independent t-test, and paired sample t-test.P< 0.05 was considered statistically significant. RESULTS: The mean score of FSFI in the intervention group was increased from 12.70 ± 6.166 before the onset of the intervention to 17.36 ± 5.407 after 8 weeks (P = 0.01). In the control group, the mean score of FSFI was decreased from 13.09 ± 4.306 to 12.29 ± 3.511 on the 8th week postpartum (P = 0.06). The mean times of sexual intercourse resumption in the intervention and control groups were 5.82 ± 0.17 and 5.81 ± 0.22 weeks, respectively, which were not significantly different between the two groups (P = 0.879). CONCLUSION: Sexual health education for women in the postpartum period could improve their sexual function after childbirth. However, it is recommended to use sexual health education programs in women during the postpartum period to promote female sexual function.